2013
DOI: 10.1101/gad.223834.113
|View full text |Cite
|
Sign up to set email alerts
|

Lamin B1 depletion in senescent cells triggers large-scale changes in gene expression and the chromatin landscape

Abstract: Senescence is a stable proliferation arrest, associated with an altered secretory pathway, thought to promote tumor suppression and tissue aging. While chromatin regulation and lamin B1 down-regulation have been implicated as senescence effectors, functional interactions between them are poorly understood. We compared genome-wide Lys4 trimethylation on histone H3 (H3K4me3) and H3K27me3 distributions between proliferating and senescent human cells and found dramatic differences in senescence, including large-sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
455
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 473 publications
(469 citation statements)
references
References 61 publications
13
455
0
1
Order By: Relevance
“…Given the exquisite responsiveness of chromatin modifiers to metabolic cues, the metabolic control of healthspan should reasonably involve a similar regulation of the epigenome (López‐Otín et al., 2016). Our current findings suggest that the healthspan‐promoting capacity of metformin might involve not only an indirect regulation of metabolo‐epigenetic fluxes, but also a direct targeting of key aging/senescence‐related chromatin regulators such as the H3K27me3 histone demethylase KDM6A/UTX (Jin et al., 2011; Maures, Greer, Hauswirth & Brunet, 2011; McCauley & Dang, 2014; Shah et al., 2013). A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the exquisite responsiveness of chromatin modifiers to metabolic cues, the metabolic control of healthspan should reasonably involve a similar regulation of the epigenome (López‐Otín et al., 2016). Our current findings suggest that the healthspan‐promoting capacity of metformin might involve not only an indirect regulation of metabolo‐epigenetic fluxes, but also a direct targeting of key aging/senescence‐related chromatin regulators such as the H3K27me3 histone demethylase KDM6A/UTX (Jin et al., 2011; Maures, Greer, Hauswirth & Brunet, 2011; McCauley & Dang, 2014; Shah et al., 2013). A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Our current findings suggest that the healthspan‐promoting capacity of metformin might involve not only an indirect regulation of metabolo‐epigenetic fluxes, but also a direct targeting of key aging/senescence‐related chromatin regulators such as the H3K27me3 histone demethylase KDM6A/UTX (Jin et al., 2011; Maures, Greer, Hauswirth & Brunet, 2011; McCauley & Dang, 2014; Shah et al., 2013). A decrease in repression‐associated H3K27me3 (and an increased activity of the H3K27me3 demethylase KDM6A/UTX) is a key feature of the global chromatin reconfiguration occurring not only in somatic cells during the normal aging process but also in prematurely aging cells in HGPS and WS (Scaffidi & Misteli, 2005; Shah et al., 2013; Shumaker et al., 2006). In addition, landmark observations in Caenorhabditis elegans have linked gain of H3K27me3 (and loss of the H3K27me3 demethylase UTX‐1) to extended longevity, strongly suggesting that preserving high levels of H3K27me3 by inhibiting KDM6/UTX may be critical for maintaining youthfulness (Jin et al., 2011; Maures et al., 2011; McCord et al., 2013; Shah et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,[9][10][11] Recently, it has been shown that repressive markers, such as H3K9me3, H3K9me2 and H3K27me3, are rearranged into the nonoverlapping structural layers in SAHF. [12][13][14] Changes of heterochromatin organization generate a repressive chromatin environment that prevents transcription of genes that promote growth, thereby stabilize the state of senescence. 7,15 The retinoblastoma (RB) tumor suppressor is an important senescence regulator, which is typically activated during senescence and enforces the expression of other senescence-inducing proteins.…”
mentioning
confidence: 99%
“…2 Large chromatin domains with similar properties have also been identified by chromatin immunoprecipitation (ChIP) of lamin A/C (referred to here as LMNA) or lamin B1 (LMNB1) coupled to array hybridization 12 or highthroughput sequencing (ChIP-seq). [13][14][15] The published datasets reveal significant overlap in genomic coverage of lamin-interacting domains discovered by DamID and ChIP 15 despite differences between the 2 methods. 16 In the ChIP assay, 17 chromatin is fractionated into »200-500 base pair (bp) fragments usually by sonication in buffer containing an ionic detergent such as sodium dodecylsulfate, 18 or by enzymatic digestion with micrococcal nuclease (MNase).…”
Section: Introductionmentioning
confidence: 99%